Deteksi Gen Resistensi Aeromonas hydrophila yang Diisolasi dari Budidaya Ikan Lele Di Jambi - wulandari, titis; Wiyoko, Tri; Agrita, Tri Wera; Hermana, Nabila Swarna Puspa; Indrawati, Agustin (Postgraduate, University of Mataram, 2024)
Aeromonas hydrophila is one of the causative agents for Motile Aeromonas Septicemia (MAS) in catfish. MAS treatment is generally carried out by administering antibiotics. This study aimed to determine the antibiotic resistance profile of A. hydrophila and detect the presence of resistance genes. The samples are archived A. hydrophila isolates isolated from catfish ponds in the district of Muara Jambi, Bungo, Jambi Province, and Merangin total of 18 isolates. Testing the antibiotic resistance profile was carried out using the disk diffusion method against tetracycline, oxytetracycline, ampicillin, amoxicillin, ciprofloxacin, enrofloxacin, and streptomycin. The detected resistance genes were ampC, qnrA, qnrB, and qnrS. The results showed A. hydrophila isolates were resistant to tetracycline (100%), oxytetracycline (94.42%), ampicillin (77.70%), and amoxicillin (77.72%) and still sensitive to ciprofloxacin (83.32%), enrofloxacin (100 %), and streptomycin (100%). The ampC gene was found in 8 out of 14 isolates resistant to beta-lactam antibiotics (57.14%). The qnrA and qnrS genes were found in 3 out of 4 isolates resistant to quinolone antibiotics (75%), while qnrB was found in 1 isolate (25%). A. hydrophila isolated from catfish ponds in Jambi develops resistance to antibiotics and resistance genes found in isolates resistant to antibiotics.